ASSESSING STUDENTS’ SELF EFFICACY IN SCIENCE LEARNING - Multi Armainah; Windy Amelia Rizki; Rahma Alia Kasih; Rahmi Alisa Putri; Widia Kemala Sari; Fatma Wati (Pendidikan IPA, FMIPA, UNP, 2022)
Self efficacy is an individual's assessment about his ability to organize, manage, and execute a series of behaviors to get the results he wants to achieve. Science learning at school is one of the ways to build up students character through learning activities. This study aims to assess students' self efficacy in science learning and examine male students and female students difference in term of their self efficacy. The research method used is descriptive research with quantitative approach. The instrument was distributed to 38 students which consisted of 12 (twelve) statements with 4 Likert Scale options. The results showed that students have very strong sense of self efficacy with 84,3%. Also, male and female students performed similar sense of self efficacy.